Validity and Reliability of the Medical Student e-Learning Management System Readiness Scale - Agus Sugiharto; Wastucitra Cantika; Retno Asti Werdhani (Jurnal Pendidikan Indonesia Gemilang, 2023)
The degree to which a person is seen as having the attitudes and traits necessary for success in studies in the future is known as e-learning management system (EMAS) ready. This study evaluated the EMAS preparation measure for medical students. The study's methodology makes use of the Borg and Gall five-step streamlined research design. The EMAS preparedness scale is measured using ten items and five dimensions. 117 students at the Faculty of Medicine, at a public university in Depok, Indonesia, were given the questionnaire. the relationship between the reliability test, Cronbach's Alpha, and the validity test, Pearson's Product Moment. These are the study's findings: All items had values of α .05, testing the instrument's validity on 10 item questions indicates that all question items are declared valid with a value greater than r table 0.1816. While test reliability indicates an alpha value of Cronbach 0.678, the tested instrument can be declared reliable or consistent. According to the results, ten items possessed high validity and reliability.